Dinitrosyl iron complexes with cysteine. kinetics studies of the formation and reactions of dnics in aqueous solution - Pereira, Jose Clayston Melo [UNESP]; Iretskii, Alexei V.; Han, Rui-min; Ford, Peter C. (American Chemical Society (ACS), 2014)
Kinetics studies provide mechanistic insight regarding the formation of dinitrosyl iron complexes (DNICs) now viewed as playing important roles in the mammalian chemical biology of the ubiquitous bioregulator nitric oxide (NO). Reactions in deaerated aqueous solutions containing FeSO4, cysteine (CysSH), and NO demonstrate that both the rates and the outcomes are markedly pH dependent. The dinuclear DNIC Fe2(μ-CysS)2(NO)4, a Roussin’s red salt ester (Cys-RSE), is formed at pH 5.0 as well as at lower concentrations of cysteine in neutral pH solutions. The mononuclear DNIC Fe(NO)2(CysS)2 − (Cys-DNIC) is produced from the same three components at pH 10.0 and at higher cysteine concentrations at neutral pH. The kinetics studies suggest that both Cys-RSE and Cys-DNIC are formed via a common intermediate Fe(NO)(CysS)2 −. Cys-DNIC and Cys-RSE interconvert, and the rates of this process depend on the cysteine concentration and on the pH. Flash photolysis of the Cys-RSE formed from Fe(II)/NO/cysteine mixtures in anaerobic pH 5.0 solution led to reversible NO dissociation and a rapid, second-order back reaction with a rate constant kNO = 6.9 × 107 M−1 s −1 . In contrast, photolysis of the mononuclear-DNIC species Cys-DNIC formed from Fe(II)/ NO/cysteine mixtures in anaerobic pH 10.0 solution did not labilize NO but instead apparently led to release of the CysS• radical. These studies illustrate the complicated reaction dynamics interconnecting the DNIC species and offer a mechanistic model for the key steps leading to these non-heme iron nitrosyl complexes.